Educational Legislation and Parental Motivation for becoming Involved in Education: A Comparative Analysis between Israel and Quebec-Canada - Schaedel, Bruria; Deslandes, Rollande; Eshet, Yovav (International Journal about Parents in Education, 2023)
The increasing evidence regarding school-family collaboration, as a means to improve school effectiveness, student perseverance and academic achievement, has encouraged many countries around the globe to endorse legislation and policies to facilitate and augment greater school-family levels of participation. However, in previous studies the macro educational and legislative environments were not correlated to the motivational inclinations of parents. Based on a study recently conducted in Israel, this comparative analysis underlines the evolution of legislation and government policies in Israel and Québec-Canada. This analysis will present the similarities and differences between the key findings highlighted in the two educational systems. We will explore the extent to which state legislative policies motivate parental partnership in schools and at home. We will suggest changes that should be implemented in both countries, within schools and at regional levels. This will call for increased focus on teacher-parent cooperation to foster bonds between schools and parents.  Finally, we will recommend urgently-required reforms in the Israeli legislation system to advance parental involvement in education and possibly mitigate currently existing achievement gaps